Nano titanium-based antireflection self-cleaning material and preparation method thereof
By preparing nano -titanium -based reflection self -cleaning materials on the surface of photovoltaic components, the lack of reflection and anti -gray performance of photovoltaic component coating materials is solved. Water self -cleaning performance.
Patent Information
- Application Number
- CN202411646800.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-28
AI Technical Summary
The existing photovoltaic module coating materials lack anti-reflection and anti-ash performance, and poor ductility on the surface of the photovoltaic module, resulting in reduced efficiency and difficulty in cleaning of the photovoltaic module.
By mixing TIO2 solution with pH as a neutral SIO2 solution, and adding inorganic silicate flow variables, nano -titanium -based reflection self -cleaning materials are prepared. The material is made of a photovoltaic component surface at the temperature of the photovoltaic component at room temperature, achieving reflection, anti -static anti -falling ash, and super -consuming water self -cleaning performance.
The broadband reduction reflection, antistatic anti -off -proof and super -proof water self -cleaning performance of the surface of photovoltaic components, improved the photovoltaic conversion efficiency of photovoltaic components, reduced the frequency of cleaning, and extended the service life of the material.
Smart Images

Figure CN119371843A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of photocatalytic functional coating materials, and relates to a nano titanium-based anti-reflection self-cleaning material and a preparation method thereof. Background Art
[0002] Photovoltaic modules are in harsh outdoor environments for a long time. Due to Fresnel reflection, surface dust accumulation, and pollutant adhesion, the efficiency of photovoltaic modules is reduced, the service life is shortened, and the cleaning is difficult and the operation and maintenance cost is high. These problems have become the industry pain points faced by the current photovoltaic power stations. The self-cleaning functional anti-reflection coating combines optical anti-reflection performance with self-cleaning performance, which can effectively inhibit dust adhesion, reduce solar energy loss caused by interface reflection, improve the photoelectric conversion efficiency of photovoltaic modules, and significantly reduce the cleaning frequency. However, the curing process of photovoltaic glass coating requires high-temperature calcination to ensure the firmness of the coating, which is difficult to meet the needs of large-area, low-cost and high-efficiency applications of photovoltaic modules. Chinese patent ZL201910155427.1 discloses a method for preparing a titanium dioxide super-hydrophilic self-cleaning photocatalytic film by a modified PTA method. The prepared film has excellent super-hydrophilic self-cleaning performance and high light transmittance, and does not require high-temperature treatment. It can be fixed on the surface of the current photovoltaic modules or the substrate that cannot be tempered at high temperature at room temperature to achieve long-term self-cleaning function, and has a broad application space. However, the self-cleaning film has no significant anti-reflection and anti-dust properties, and it is difficult to meet the application requirements of photovoltaic modules for anti-reflection and long-term anti-fouling. At the same time, the photocatalytic nanosol prepared by this method uses water as the main solvent and has limited ductility. When loaded on the surface of the current photovoltaic modules, it is very easy to cause uneven coating, local excess, and easy icing and difficulty in drying in the low temperature environment in autumn and winter. Summary of the invention
[0003] In view of the problems existing in the prior art, the present invention provides a nano titanium-based anti-reflection self-cleaning material and a preparation method thereof, thereby solving the technical problems that the coating material in the prior art does not have the anti-reflection and anti-dust falling properties and has poor ductility on the surface of photovoltaic modules.
[0004] The present invention is achieved through the following technical solutions: A method for preparing a nano titanium-based anti-reflection self-cleaning material comprises the following steps: S1: mixing TiO2 sol with SiO2 sol with a neutral pH value to obtain a mixed sol; wherein the size of SiO2 in the SiO2 sol with a neutral pH value is nanometer-scale; S2: dispersing the mixed sol in a mixed solution of ethanol and water, stirring evenly, to obtain a mixed solution; S3: adding an inorganic silicate rheological agent to the mixed solution, stirring the mixture for reaction, and obtaining the nano titanium-based anti-reflection self-cleaning material.
[0005] Preferably, in step S1, the weight ratio of the TiO2 sol to the SiO2 sol is (0.5~5):1.
[0006] Preferably, in step S1, the particle size of SiO2 in the SiO2 sol is 5-20 nm.
[0007] Preferably, in step S2, the weight ratio of the mixed sol to ethanol and water is 1:(1-3):(1-10).
[0008] Preferably, in step S3, the inorganic silicate rheological agent is one or a combination of any two of magnesium aluminum silicate, magnesium lithium silicate and montmorillonite; the weight fraction of the inorganic silicate rheological agent in the total reaction system is 0.05% to 5%, and after adding the inorganic silicate rheological agent, the reaction is stirred for 30 to 60 minutes.
[0009] A nano titanium-based anti-reflection self-cleaning material is prepared by the method.
[0010] An anti-reflection self-cleaning coating is prepared by coating the above-mentioned nano titanium-based anti-reflection self-cleaning material on the surface of a substrate and curing it.
[0011] The above-mentioned anti-reflection self-cleaning coating, the number of coatings is 1 to 5 times, and the amount of a single coating is 20 to 60 m 2 / L.
[0012] Preferably, when the substrate is photovoltaic glass, the photovoltaic glass coated with the nano-titanium-based anti-reflection self-cleaning material has an average light transmittance of 93% to 96% at 380 nm to 1100 nm; a surface resistivity of 10 8 Ω; the static water drop contact angle on the surface is no more than 5°; after 400 washes, the photovoltaic transmittance loss is no more than 0.2%.
[0013] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a nano titanium-based anti-reflection self-cleaning material, wherein SiO2 sol with a neutral pH value is added to TiO2 sol, and the size of SiO2 in the SiO2 sol is nanometer-level. SiO2 sol with a neutral pH value is selected here, and its performance is milder and its application range is wider; in addition, nanometer-level SiO2 sol has a lower refractive index, which can reduce the reflection of light on the surface of the material, thereby increasing the utilization rate of light energy. Adding an inorganic silicate rheological agent to the system has multiple effects on improving the performance of functional coatings, simplifying the preparation process, and reducing costs. First, the inorganic silicate rheological agent forms a colorless and transparent liquid after dissolving, which does not affect the transparency of the coating solution. It is of great significance in application scenarios where transparency needs to be maintained, such as the field of optical thin films. Secondly, the inorganic silicate rheological agent can form a three-dimensional network structure in the coating solution system, enhance the uniformity and stability of the dispersion of TiO2 and SiO2 nanoparticles in the coating solution, and its unique rheological properties help control the viscosity of the coating coating solution, making it easier to form a film on the surface of the substrate at low temperature, construct a micro-nano structure with a certain nano-scale roughness, and further enhance the anti-reflection effect. Thirdly, the structure can form a conductive network, so that the charge can move and disperse more effectively inside and on the surface of the material, thereby accelerating the leakage of static charge, reducing surface static electricity accumulation, and providing the coating material with moderate antistatic properties to achieve antistatic and anti-dust effects. Finally, compared with other conductive particles, the inorganic silicate rheological agent has the advantages of low addition, long-term effect and low cost when achieving antistatic effects. The preparation method is simple and reasonably designed, and effectively improves the low-temperature film-forming, anti-reflective and anti-dust properties of the coating material.
[0014] Furthermore, another inventive point of the present invention is that in step S1, the weight ratio of the TiO2 sol to the SiO2 sol is (0.5-5):1. First, the composite use of SiO2 and TiO2 can effectively reduce the reflection of light on the surface of the transparent substrate. SiO2 has a lower refractive index, while the refractive index of TiO2 is relatively high. By adjusting the weight ratio of TiO2 to SiO2, the refractive index of the composite material can be accurately controlled, which helps to reduce the reflection of light on the surface of the material, thereby increasing the transmitted light intensity and achieving a better anti-reflection effect. Secondly, TiO2 has excellent photocatalytic properties and can decompose organic pollutants under sunlight and make the surface show Super hydrophilicity, achieving surface self-cleaning effect. By controlling the content of TiO2 sol, the photocatalytic performance of the composite material can be optimized, so that it has stronger self-cleaning ability while maintaining the anti-reflection effect; third, the coating with micro-nano structure formed by the composite of SiO2 and TiO2 has high stability and corrosion resistance, which is crucial for applications such as photovoltaic panels exposed to outdoor environments for a long time; fourth, SiO2 sol can also be used as an inorganic binder to evenly disperse TiO2 nanoparticles to prevent their agglomeration and sedimentation. The appropriate weight ratio of TiO2 to SiO2 sol helps to form a more stable dispersion system and improve the uniformity and stability of the composite material. By compounding SiO2 and TiO2 in proportion, the anti-reflection and self-cleaning properties of the functional coating are adjusted, which plays an important role in the practical application of coating materials under outdoor conditions.
[0015] Furthermore, another inventive point of the present invention is that in step S1, the particle size of SiO2 in the SiO2 sol is 5-20 nm. First, when the particle size of SiO2 in the SiO2 sol is 5-20 nm, When the size of nano-SiO2 particles is within the range of 1.34 nm, these tiny nanoparticles can effectively reduce the reflection of light on the surface of the material, thereby increasing the intensity of transmitted light. This anti-reflection effect is of great significance for improving the photoelectric conversion efficiency of solar cells, improving the light transmittance of architectural glass and automobile windshields, etc. Due to the size effect of nano-SiO2 particles, they can scatter and absorb ultraviolet rays more effectively, while allowing more visible light to pass through. This characteristic makes nano-titanium-based anti-reflection self-cleaning materials have broad application prospects in the optical field; secondly, the addition of nano-SiO2 particles can enhance the mechanical properties of the material, such as hardness, wear resistance and scratch resistance. The improvement of these properties helps to extend the service life of the material and improve its durability in practical applications. Nano-SiO2 particles have a high specific surface area and strong chemical bonding ability, and can form a stable chemical bond with the nanoparticles in the TiO2 sol. This chemical bond helps to improve the overall stability of the composite material and prevent the coating from aging and falling off due to wear during use; in addition, when the SiO2 particle size in the SiO2 sol is moderate, it can form a synergistic effect with the TiO2 sol to enhance the photocatalytic performance of the composite material. Under light, TiO2 can decompose organic pollutants, while nano-SiO2 particles can provide better adsorption and dispersion effects, thereby accelerating the decomposition and removal of pollutants. The addition of nano-SiO2 particles can also improve the hydrophilicity of the material and prevent the adhesion of dust and dirt. This improvement in hydrophilicity helps to maintain the long-term self-cleaning properties of the material while extending its service life.
[0016] Furthermore, another inventive point of the present invention is that in step S2, the weight ratio of the mixed sol to ethanol and water is 1:(1~3):(1~10). First, ethanol and water as solvents can effectively dissolve and disperse the nanoparticles in the mixed sol. The appropriate solvent ratio helps to form a uniform sol system and prevent the agglomeration and sedimentation of the nanoparticles. Secondly, the appropriate solvent ratio helps to form a high-quality film. The volatilization rates of ethanol and water are different. By adjusting their ratio, the drying speed of the sol system can be accelerated, which helps to form a dense film at room temperature, reduce the influence of low temperature on the film-forming properties of the material, and avoid problems such as uneven film formation or even freezing caused by high local coating amount. Finally, the synergistic effect of ethanol and water can promote the close arrangement and interconnection of nanoparticles in the sol, improve the ductility of the material on the substrate surface, and further improve the adhesion between the film and the substrate. Good adhesion helps to prevent the film from falling off or cracking during use, and improves the stability and durability of the material.
[0017] Furthermore, another inventive point of the present invention is that in step S3, the inorganic silicate rheological agent is one or a combination of any two of magnesium aluminum silicate, magnesium lithium silicate and montmorillonite; the weight fraction of the inorganic silicate rheological agent in the total reaction system is 0.05%~5%, and the inorganic silicate rheological agent is added and the reaction is stirred for 30~60 min. First of all, for the selection of inorganic silicate rheological agents, magnesium aluminum silicate has excellent rheological and thixotropic properties, which can significantly improve the fluidity of the sol system, making it easier to coat and process. It can also act as a stabilizer, suspending agent and thickener, which helps to maintain the stability of the sol system and prevent the agglomeration and sedimentation of nanoparticles. Lithium magnesium silicate has high expansibility, thixotropy and viscosity change ability. It can form a nanoscale three-dimensional network structure in the sol system, enhance the dispersion uniformity and stability of nanoparticles in the coating solution, and the addition of lithium magnesium silicate can also improve the antistatic properties of the material and achieve antistatic and anti-dusting effects. Montmorillonite is a layered silicate mineral with excellent adsorption properties and ion exchange capacity. In the sol system, montmorillonite can be used as a carrier or filler to improve the mechanical properties and durability of the material. Secondly, the weight fraction of the inorganic silicate rheological agent in the total reaction system is 0.05%~5%. The selection of this ratio range is based on its influence on the rheology and film-forming properties of the sol system. Too little addition cannot fully exert its rheological regulation and stabilization effect, while too much addition may cause the sol system to be too viscous, which is not conducive to coating and processing. Finally, after adding the inorganic silicate rheological agent, the reaction is stirred for 30~60min. This time range is selected to ensure that the inorganic silicate rheological agent can be fully dispersed in the sol system and form stable chemical bonds with TiO2 and SiO2 nanoparticles. Sufficient stirring reaction time helps to improve the uniformity and stability of the material. Therefore, the addition of the inorganic silicate rheological agent can significantly improve the fluidity of the sol system, making it easier to coat and process, and can form a three-dimensional network structure in the sol system, enhance the dispersion uniformity, stability and antistatic properties of the nanoparticles, and improve the anti-reflection and adhesion of the material after film formation.
[0018] The present invention also provides an anti-reflection self-cleaning coating, which is obtained by coating the above-prepared nano titanium-based anti-reflection self-cleaning material on the surface of a substrate and curing it at room temperature. The substrate can be a transparent substrate or an opaque substrate, and the number of coatings is 1 to 5 times. When coating once, the amount used is 20 to 60 m 2 / L, this method is simple to operate and cost-controlled. The material can be coated by simple rolling or spraying. At the same time, the number of coatings can be controlled to 1 to 5 times, and the dosage for a single coating is 20 to 60 m 2 / L can ensure that the coating has an appropriate thickness. A coating that is too thick will cause incomplete drying, cracking or falling off, while a coating that is too thin will not provide sufficient protective performance. In addition, an appropriate amount of single coating helps to improve material utilization and reduce waste. Excessive dosage will increase material costs, while too little dosage may cause uneven coating or fail to completely cover the substrate surface. By controlling the parameters in the coating process, a coating with excellent performance can be obtained.
[0019] In addition, the nano-titanium-based anti-reflection self-cleaning coating prepared by the present invention is applied to the surface of a transparent substrate using simple spraying, wiping and other process scales, and exhibits excellent broadband anti-reflection, anti-static dust prevention and super-hydrophilic self-cleaning properties, and has broad application prospects. The coating material can be widely used on the surface of transparent substrates, such as ordinary glass, photovoltaic modules, etc., at room temperature, reflecting its low production and manufacturing costs and wide range of applications; the average light transmittance of the coating material in the 380 nm~1100 nm band is 93%~96%, which is significantly higher than ordinary glass and photovoltaic glass, showing excellent anti-reflection performance, that is, improving the utilization rate of sunlight by the substrate, which is of great significance for improving the power generation efficiency of photovoltaic modules; the surface resistivity of the coating material is 10 8 Ω, reflecting its excellent antistatic performance, which can effectively reduce the generation and accumulation of surface static electricity, inhibit the adsorption of dust by the substrate, and achieve the effect of preventing dust from falling. It plays an important role in ensuring the light transmittance of the substrate, improving the utilization rate of solar energy, and avoiding the performance loss caused by the hot spot effect caused by dust accumulation. The surface static water droplet contact angle of the coating material is not more than 5°, showing significant super-hydrophilic self-cleaning performance, that is, the water droplets can quickly spread on the glass surface to form a uniform water film, thereby effectively removing the dust and stains on the surface. At the same time, the hydrophilicity is combined with the photocatalytic activity of the nano-titanium-based material. It can promote the decomposition of organic pollutants on the surface and achieve long-term self-cleaning performance. This feature allows the substrate to maintain self-cleaning and light transmittance when exposed to outdoor environments for a long time, reducing the frequency and cost of manual cleaning. In addition, after the coating material is formed on the surface of photovoltaic glass, after 400 washings, the photovoltaic transmittance loss is no more than 0.2%. It can be seen that the coating material has excellent wear resistance and stability in practical applications. Even in frequent use and cleaning, it can still maintain excellent light transmittance. This feature verifies the reliability and durability of the coating material and its room temperature coating process in practical applications. These functional characteristics make it have potential application value in many fields, especially in the large-scale application of existing photovoltaic systems. The coating material significantly improves the light transmittance, anti-static and anti-dust performance, super-hydrophilic self-cleaning performance and durability of photovoltaic glass, which helps to improve the power generation efficiency of photovoltaic panels and reduce the operation and maintenance costs of photovoltaic enterprises, with significant technical and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 It is a schematic flow chart of a method for preparing a nano titanium-based anti-reflection self-cleaning material in the present invention; Figure 2 This is a comparison chart of the light transmittance of the nano-titanium-based anti-reflection self-cleaning coating glass prepared in Example 1 and blank glass; Figure 3 The contact angle of a water drop on the glass surface of the nano-titanium-based anti-reflection self-cleaning coating prepared in Example 1; Figure 4 A comparison chart of the resistivity of the glass surface with the nano-titanium-based anti-reflection self-cleaning coating prepared in Example 2 and that of the blank glass surface; Figure 5 Photovoltaic transmittance of the nano-titanium-based anti-reflection self-cleaning coating glass prepared in Example 2 before and after washing. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0023] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0024] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0025] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0026] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0027] like Figure 1 As shown, the present invention provides a method for preparing a nano titanium-based anti-reflection self-cleaning material, comprising the following steps: S1: at room temperature, mixing TiO2 sol with SiO2 sol with a neutral pH value to obtain a mixed sol; wherein the size of SiO2 in the SiO2 sol with a neutral pH value is nanometer-scale; The weight ratio of the TiO2 sol to the SiO2 sol is (0.5-5): 1. Preferably, in the SiO2 sol, the particle size of SiO2 is 5-20 nm, the content of SiO2 is 30±5%, and the SiO2 sol with a neutral pH is purchased from Zhejiang Yuda Chemical Co., Ltd.
[0028] S2: dispersing the mixed sol in a mixed solution of ethanol and water, stirring for 10 to 30 min to obtain a mixed solution; The weight ratio of the mixed sol to ethanol and water is 1:(1-3):(1-10).
[0029] S3: adding an inorganic silicate rheological agent to the mixed solution, stirring and reacting for 30 to 60 minutes, and obtaining the nano titanium-based anti-reflection self-cleaning material.
[0030] The inorganic silicate rheological agent is one of magnesium aluminum silicate, magnesium lithium silicate and montmorillonite or a combination of any two thereof; the weight fraction of the inorganic silicate rheological agent in the total reaction system is 0.05% to 5%.
[0031] The solid content of the nano titanium-based anti-reflection self-cleaning material prepared by the above method is 0.5% to 10%.
[0032] The preparation of TiO2 sol in the present invention refers to Chinese patent ZL201910155427.1.
[0033] Then, the nano titanium-based anti-reflection self-cleaning material prepared above can be fixed on the surface of the substrate to form a film by wiping, scraping or spraying at room temperature, and then repeated coating after natural drying, wherein the amount of coating solution used for a single time is 20~60m 2 / L, the coating times are 1 to 5 times. The substrate can be glass or a photovoltaic panel, and a self-cleaning glass or a photovoltaic panel with good performance is obtained.
[0034] The present invention uses the TiO2 sol prepared by the modified PTA method in Chinese patent ZL201910155427.1 as the substrate, and can control the preparation of environmentally friendly, stable, low-energy-consuming, and high-yield nano-titanium-based anti-reflection self-cleaning coating liquid by means of nano-size-matched low-refractive-index SiO2 nanoparticle composites and multi-functional inorganic silicate rheological agent modification; through wiping, scraping and spraying processes, a composite functional nano coating with broadband anti-reflection, anti-static dust prevention, and super-hydrophilic self-cleaning properties is loaded on the surface of the substrate at room temperature, which has the advantages of simple process and easy promotion; In addition, the addition of the inorganic silicate rheological agent in the present invention has multiple functions. On the one hand, the inorganic silicate rheological agent can be evenly dispersed in the mixed sol of TiO2 and SiO2 to form a certain three-dimensional network structure, enhance the uniformity and stability of the dispersion of nanoparticles in the plating solution, make it easier to form a film on the surface of the substrate at low temperature, and construct a micro-nano structure with a certain nano-scale roughness to achieve an anti-reflection effect; on the other hand, conventional conductive particles (such as metal oxides, silver, copper and other metal powders) may be unevenly distributed in the material, resulting in inconsistent antistatic properties, while inorganic silicates such as magnesium aluminum silicate provide moderate antistatic effects, which can provide the film layer with more uniform and lasting antistatic properties to achieve antistatic and anti-dusting effects, and are lower in cost and more environmentally friendly.
[0035] In addition, the nano-titanium-based anti-reflection self-cleaning coating prepared by the present invention can be applied to the surface of existing photovoltaic glass at room temperature using simple spraying, wiping and other processes, showing excellent broadband anti-reflection, anti-static dust prevention and super-hydrophilic self-cleaning properties. When the film is formed on photovoltaic glass, the average light transmittance in the visible light range of 380 nm to 800 nm is 94% to 96%, which is about 3% higher than that of a simple substrate, and the surface resistivity is 10 8 Ω, showing anti-static and anti-dust performance, the static water droplet contact angle on the surface is no more than 5°, and it has excellent super hydrophilic self-cleaning performance; in addition, the photovoltaic transmittance loss of the coating is no more than 0.2% after 400 washings, which has significant performance advantages and broad application prospects in the field of low-temperature preparation of photovoltaic functional coatings.
[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0037] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0038] Example 1 A method for preparing a nano titanium-based anti-reflection self-cleaning coating comprises the following steps: (1) At room temperature, the TiO2 sol prepared by the modified PTA method and the neutral SiO2 sol were mixed in a weight ratio of 1:1; (2) The mixed sol is dispersed in an ethanol / water solution, wherein the weight ratio of the mixed sol, ethanol and water is 1:1:5; after being evenly mixed, 0.5% of magnesium aluminum silicate is added, and the mixture is stirred for reaction for 60 minutes to obtain a coating solution; (3) At room temperature, the coating liquid is applied to the surface of the photovoltaic glass using a spraying process. The amount of coating liquid used is about 30 m 2 / L, and dried naturally to obtain a single-layer antistatic, anti-reflective, self-cleaning composite functional coating.
[0039] The light transmittance comparison between the prepared single-layer nano-titanium-based anti-reflection self-cleaning coating and blank glass is shown in Figure 2 ,Depend on Figure 2 It can be seen that the glass coated with the nano-titanium-based anti-reflection self-cleaning coating has good light transmittance.
[0040] The surface contact angle of water droplets on the prepared single-layer nano-titanium-based anti-reflection self-cleaning coating is about 5°. Figure 3 As shown, it has good self-cleaning performance.
[0041] Example 2 A method for preparing a nano titanium-based anti-reflection self-cleaning coating comprises the following steps: (1) At room temperature, the TiO2 sol prepared by the modified PTA method and the neutral SiO2 sol were mixed in a weight ratio of 1:2; (2) The mixed sol is dispersed in an ethanol / water solution, wherein the weight ratio of the mixed sol, ethanol and water is 1:2:4; after being evenly mixed, 0.5% of magnesium aluminum silicate is added, and the mixture is stirred for reaction for 60 min to obtain a coating solution; (3) At room temperature, the coating liquid is applied to the surface of the photovoltaic glass using a scraping process. The amount of coating liquid used is about 60 m 2 / L, and repeat the coating twice after natural drying to obtain multiple layers of nano-titanium-based anti-reflective self-cleaning coating.
[0042] The prepared multilayer antistatic antireflective self-cleaning composite functional coating has good antistatic performance and a surface resistivity of 10 8 Ω, such as Figure 4 As shown; after the coating was washed 400 times, the photovoltaic transmittance remained basically unchanged (from 93.5% to 93.4%), as shown Figure 5 As shown, it has excellent scrub resistance and good stability.
[0043] Example 3 A method for preparing a nano titanium-based anti-reflection self-cleaning material comprises the following steps: S1: At room temperature, TiO2 sol is mixed with SiO2 sol with a neutral pH to prepare a mixed sol; The weight ratio of the TiO2 sol to the SiO2 sol is 0.5:1. In the SiO2 sol, the average particle size of SiO2 is 5 nm and the content of SiO2 is 28%.
[0044] S2: dispersing the mixed sol in a mixed solution of ethanol and water, stirring for 10 min to obtain a mixed solution; the weight ratio of the mixed sol to ethanol and water is 1:1:1.
[0045] S3: adding an inorganic silicate rheological agent to the mixed solution, stirring and reacting for 30 minutes, to obtain the nano titanium-based anti-reflection self-cleaning material.
[0046] The inorganic silicate rheological agent is magnesium aluminum silicate; the weight fraction of the inorganic silicate rheological agent in the total reaction system is 0.05%.
[0047] Then, at room temperature, the prepared nano titanium-based anti-reflection self-cleaning material was fixed on the surface of ordinary glass by blade coating. The coating times were 3 times, and the amount of coating solution used for each coating was 25 m 2 / L, during the coating process, the single layer is naturally dried and then repeatedly coated to obtain glass with self-cleaning function and good light transmittance.
[0048] Example 4 A method for preparing a nano titanium-based anti-reflection self-cleaning material comprises the following steps: S1: At room temperature, TiO2 sol is mixed with SiO2 sol with a neutral pH to prepare a mixed sol; The weight ratio of the TiO2 sol to the SiO2 sol is 5: 1. In the SiO2 sol, the average particle size of SiO2 is 20 nm, and the content of SiO2 is 35%.
[0049] S2: dispersing the mixed sol in a mixed solution of ethanol and water, stirring for 30 min to obtain a mixed solution; the weight ratio of the mixed sol to ethanol and water is 1:3:10.
[0050] S3: adding an inorganic silicate rheological agent to the mixed solution, stirring and reacting for 60 minutes, to obtain the nano titanium-based anti-reflection self-cleaning material.
[0051] The inorganic silicate rheological agent is lithium magnesium silicate; the weight fraction of the inorganic silicate rheological agent in the total reaction system is 0.5%.
[0052] Then, the prepared nano titanium-based anti-reflection self-cleaning material can be fixed on the surface of ordinary glass by spraying process at room temperature. The coating times are 5 times, and the amount of coating liquid used for a single time is 20 m 2 / L, during the coating process, the single layer is naturally dried and then repeatedly coated to obtain glass with self-cleaning function and good light transmittance.
[0053] Example 5 A method for preparing a nano titanium-based anti-reflection self-cleaning material comprises the following steps: S1: At room temperature, TiO2 sol is mixed with SiO2 sol with a neutral pH to prepare a mixed sol; The weight ratio of the TiO2 sol to the SiO2 sol is 2: 1. In the SiO2 sol, the average particle size of SiO2 is 10 nm, and the content of SiO2 is 31%.
[0054] S2: dispersing the mixed sol in a mixed solution of ethanol and water, stirring for 20 min to obtain a mixed solution; the weight ratio of the mixed sol to ethanol and water is 1:2:5.
[0055] S3: adding an inorganic silicate rheological agent to the mixed solution, stirring and reacting for 50 minutes, to obtain the nano titanium-based anti-reflection self-cleaning material.
[0056] The inorganic silicate rheological agent is lithium magnesium silicate; the weight fraction of the inorganic silicate rheological agent in the total reaction system is 0.1%.
[0057] Then, at room temperature, the prepared nano titanium-based anti-reflection self-cleaning material was fixed on the surface of ordinary glass by wiping process. The coating times were 2 times, and the amount of coating solution used for a single time was 40 m 2 / L, during the coating process, the single layer is naturally dried and then repeatedly coated to obtain glass with self-cleaning function and good light transmittance.
[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a nano titanium-based anti-reflection self-cleaning material, characterized in that: The following steps are involved: S1: mixing TiO2 sol with SiO2 sol with a neutral pH value to obtain a mixed sol; wherein the size of SiO2 in the SiO2 sol with a neutral pH value is nanometer-scale; S2: dispersing the mixed sol in a mixed solution of ethanol and water, stirring evenly, to obtain a mixed solution; S3: adding an inorganic silicate rheological agent to the mixed solution, stirring the mixture for reaction, and obtaining the nano titanium-based anti-reflection self-cleaning material.
2. The method for preparing a nano titanium-based anti-reflection self-cleaning material according to claim 1, characterized in that: In step S1, the weight ratio of the TiO2 sol to the SiO2 sol is (0.5~5):
1.
3. The method for preparing a nano titanium-based anti-reflection self-cleaning material according to claim 1, characterized in that: In step S1, in the SiO2 sol, the particle size of SiO2 is 5-20 nm.
4. The method for preparing a nano titanium-based anti-reflection self-cleaning material according to claim 1, characterized in that: In step S2, the weight ratio of the mixed sol to ethanol and water is 1:(1-3):(1-10).
5. The method for preparing a nano titanium-based anti-reflection self-cleaning material according to claim 1, characterized in that: In step S3, the inorganic silicate rheological agent is one or a combination of any two of magnesium aluminum silicate, magnesium lithium silicate and montmorillonite; the weight fraction of the inorganic silicate rheological agent in the total reaction system is 0.05% to 5%, and after adding the inorganic silicate rheological agent, the reaction is stirred for 30 to 60 minutes.
6. A nano titanium-based anti-reflection self-cleaning material, characterized in that: Prepared by any one of claims 1 to 5.
7. An anti-reflective self-cleaning coating, characterized in that: The nano titanium-based anti-reflection self-cleaning material described in claim 6 is coated on the surface of a substrate and cured to obtain the product.
8. The anti-reflection self-cleaning coating according to claim 7, characterized in that: The number of times of coating is 1 to 5 times, and the amount of coating per time is 20 to 60 m 2 / L.
9. The anti-reflection self-cleaning coating according to claim 7, characterized in that: When the substrate is photovoltaic glass, the photovoltaic glass coated with the nano-titanium-based anti-reflection self-cleaning material has an average transmittance of 93% to 96% at 380 nm to 1100 nm; a surface resistivity of 10 8 Ω; the static water drop contact angle on the surface is no more than 5°; after 400 washes, the photovoltaic transmittance loss is no more than 0.2%.
Citation Information
Patent Citations
Preparation of superhydrophilic self-cleaning titanium dioxide photocatalytic thin films by modified PTA method
CN109734327B
Cited By
Antifouling fireproof glass decoration panel and preparation method thereof
CN119954405A
Antifouling fire-resistant glass decorative panel and preparation method thereof
CN119954405B